Depth‐dependent rupture mode along the Ecuador‐Colombia subduction zone. Issue 5 (11th March 2017) - Yoshimoto, Masahiro; Kumagai, Hiroyuki; Acero, Wilson; Ponce, Gabriela; Vásconez, Freddy; Arrais, Santiago; Ruiz, Mario; Alvarado, Alexandra; Pedraza García, Patricia; Dionicio, Viviana; Chamorro, Orlando; Maeda, Yuta; et al.
Abstract: A large earthquake ( Mw 7.7) occurred on 16 April 2016 within the source region of the 1906 earthquake in the Ecuador‐Colombia subduction zone. The 1906 event has been interpreted as a megathrust earthquake ( Mw 8.8) that ruptured the source regions of smaller earthquakes in 1942, 1958, and 1979 in this subduction. Our seismic analysis indicated that the spatial distribution of the 2016 earthquake and its aftershocks correlated with patches of high interplate coupling strength and was similar to those of the 1942 earthquake and its aftershocks, suggesting that the 2016 and 1942 earthquakes ruptured the same asperity. Our analysis of tsunami waveforms of the 1906 event indicated Mw around 8.4 and showed that large slip occurred near the trench off the source regions of the above three historical and the 2016 earthquakes, suggesting that a depth‐dependent complex rupture mode exists along this subduction zone. Key Points: The 2016 Ecuador earthquake was analyzed by using regional and global broadband seismic data Source slip inversion of the 1906 earthquake was performed by using far‐field tsunami waveforms Large slip of the 1906 earthquake ( Mw 8.4) occurred near the trench off the source regions of the 2016 and other historical earthquakes